Women in the Public Sphere and Religious Discourse Interpretation in the Post-Conflict Aceh - Mubarrak, Husni; Yahya, Faisal (Mazahib, 2020)
This article aims to discuss women and their access to the public sphere after a long term of the last three decades of armed conflict in Aceh. As many occurred in the other most conflict regions, women are mostly victims of any regime policies, either in political or economic access. This article would like to elaborate more on how women's position perceived within Acehnese society in the post-conflict Aceh since 2005? Furthermore, how are religious doctrines being interpreted regarding women’s issues in the post-conflict Aceh? By combining literature reviews and interviews as the primary source of data collection, this article argues that the long army conflict in Aceh and unfortunate Aceh's current political context are the leading cause of women's position degradation in Aceh and not because of the religious interpretation contestation. Thus, even though the formal sharia implementation has taken place in Aceh since 2002, male political domination and contestation have influenced women's position degradation in contemporary Aceh's public sphere.Keywords: Women, Post-Conflict Aceh, Sharia, Public Sphere, Religious Discourse.